Dilema dan Problematik Desain Industri di Indonesia - Sulistianingsih, Dewi; Satata, Bagas Bilowo Nurtantyono (Jurnal Suara Hukum, 2019)
Industrial design is one part of the scope of intellectual property that gets protection from the state by first registering for the design. Issues in industrial design are no less complicated with problems in the scope of other intellectual property, such as patents, brands, inventions. The clash between industrial design and copyright and brand is unavoidable. Designers must be able to understand the existence of industrial design in intellectual property. One of the problems in the body of industrial design is about renewal. The provisions of renewal are one of the reasons for the emergence of cases / cases in claims against industrial design.This study uses a normative juridical method with a legal and conceptual approach. The purpose of this study is to reveal and analyze problems in industrial design in Indonesia. A review of the Industrial Design law is important to do in order to create a law that can accommodate interests in the corridor of legal certainty, justice and expediency.